Violence Against Women and Girls in Public Transport : Policy Recommendations for Mexico City - World Bank (World Bank, Washington, DC, 2021)
Women face many barriers to using public transport services, despite representing the largest share of public transport users around the world. Transport and infrastructure-oriented barriers are related to constraints in its affordability, acceptability and availability, as well as to the physical access to public transport. There is also a recognition that there are other non-transport-related barriers that can constrain women’s mobility, such as social norms regarding gender and other more personal elements influencing women’s agency, such as self-efficacy and aspirations.